PENGEMBANGAN BUKU AJAR DRAMA BERBASIS KESENIAN LOKAL - Soleh, Dwi Rohman; Huda, Muhamad Binur (Widyabastra, 2013)
The purposes of this research are: (1) to describe the recent learning of drama in LPTK, which includes describing the application of existing drama textbooks; ( b ) describing the lecturersâ and studentsâ necessity associated with the improvement of drama textbooks in LPTK. (2) to describe the development of drama textbooks which based on local arts -, which includes : (a ) describing the development of a prototype ( draft ) into the drama textbook -based on local arts by expert judgment , (b )to describe the development and improvement of the drama textbooks based on local arts âregarded to limited testing in the research field. (3) to describe the effective level of drama textbooks based on the local arts than conventional textbooks in LPTK. (4) to describe the dissemination of drama textbook âbased the local arts. The research and development stages which are stated by Borg and Gall (1983:775) include product development, product testing in the field, and correction of products based on the data obtained after the products are tested in the research field. The outcomes of this research are: ( 1 ) learning devices including: syllabus , SAP , ( 2 ) drama textbooks based on local arts.Keywords : drama textbook, local arts